1984
DOI: 10.1093/infdis/150.6.851
|View full text |Cite
|
Sign up to set email alerts
|

Parainfluenza Virus Type 3: Seasonality and Risk of Infection and Reinfection in Young Children

Abstract: In Houston the temporal occurrence of infections with parainfluenza virus type 3 has evolved from an endemic to an epidemic pattern. Continuous virological surveillance for six years demonstrated that most infections occurred the late winter or spring after influenza virus activity. At least two-thirds of children observed in the Houston Family Study were infected with this virus in each of the first two years of life, and the risk of illness was about 30/100 children per year. After two years of age, the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
1
6

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(161 citation statements)
references
References 28 publications
10
144
1
6
Order By: Relevance
“…A regular occurrence of outbreaks associated with parainfluenza virus type 3 each year and the tendency of parainfluenza virus type 1 and 2 outbreaks to occur every second year have also been observed in England (Martin, Gardner & McQuillin, 1978) and USA (Glezen et al 1984). Similar alternations between smaller and greater RSV outbreaks as seen in Norway have also been observed in other Scandinavian countries (0rstavik et al 1984;Norwegian, Swedish and Finnish monthly reports of laboratory diagnosis of virus infections).…”
Section: Discussionmentioning
confidence: 59%
“…A regular occurrence of outbreaks associated with parainfluenza virus type 3 each year and the tendency of parainfluenza virus type 1 and 2 outbreaks to occur every second year have also been observed in England (Martin, Gardner & McQuillin, 1978) and USA (Glezen et al 1984). Similar alternations between smaller and greater RSV outbreaks as seen in Norway have also been observed in other Scandinavian countries (0rstavik et al 1984;Norwegian, Swedish and Finnish monthly reports of laboratory diagnosis of virus infections).…”
Section: Discussionmentioning
confidence: 59%
“…As observed for RSV and influenza, the seasonal pattern of HPIV infections has been described in more detail in studies from temperate areas [7,29,30]. Seasonal patterns of HPIV infections are distinct among the subtypes and geographic regions and have changed since the first descriptions of HPIV, when, in the 50's and 60's, infections by subtypes 1, 2, and 3 occurred throughout the year, in an endemic pattern.…”
Section: Discussionmentioning
confidence: 90%
“…HPIV-2 was more sporadically detected. The initial pattern of HPIV-3 was endemic, but since 1978 it has changed to epidemic with outbreaks in late winter, spring or early summer, in the United States and Australia [3,6,7,17,26,29,30]. A small number of studies have reported an epidemiology of HPIV-4.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal patterns are thus consistent with those in England and Wales. The seasonal patterns of RS virus and parainfluenza viruses 1, 2 and 3 do not appear to be different in USA (Glezen et al 1984; Kim et al 1973;Monto, Bryan & Rhodes, 1974;Monto, 1973) though a study in Michigan (Monto, 1973) stated that parainfluenza type 3 occurred in the autumn. The data provided in this paper, however, suggest that the type 3 virus is indeed a summer virus.…”
Section: Resurgent Epidemicsmentioning
confidence: 93%